Deserción en la educación superior y salud mental: Estudio bibliométrico - Véliz Palomino, José Carlos (2024)
Dropout in higher education generates significant social and economic consequences while educational research experiences an exponential growth. Bibliometric method is applied in this article, and VOSviewer and Biblioshiny software are used to analyze 340 articles on dropout and mental health in higher education obtained from the Web of Science database (2013-2023). Different methods were applied such as quote analysis, bibliographic coupling, cluster analysis, and three-field plot. Findings revealed a growing rate of research on students’ mental health compared to the rate of research on dropout in higher education, mainly in 2020-2022. Some authors, who are mostly American, are classified as productive writers on the subject matter. This study contributes to synthesizing key topics related to dropout in higher education and mental health, and enlightens new directions for future research. These are crucial findings for higher education institutions and educational policies highlighting the importance of considering students’ mental health a critical factor in student retention and the significance of building strong and stable social relations.